Outcomes of Single-Session ERCP and Cholecystectomy in the Management of Choledocholithiasis: A Pilot Retrospective Analysis (Thamar University Journal of Natural & Applied Sciences, 2025)
Background: Choledocholithiasis—the presence of gallstones in the common bile duct—remains a significant clinical concern. While ERCP and cholecystectomy are standard treatments, their sequential scheduling can increase hospitalization and costs. Objective: This pilot study evaluates the feasibility, outcomes, and complication rates of performing single-session ERCP and cholecystectomy in a resource-limited hospital setting. Methods: A retrospective analysis of 21 patients treated at Taiba Consultative Hospital (2023–2024) was conducted. Demographic, clinical, procedural, and follow-up data were analyzed. Results: ERCP had a success rate of 92.5% with a 6.8% complication rate. Cholecystectomy had an 89.3% success rate and 4.2% complication rate. The combined procedure achieved an 87.6% success rate with an 8.1% complication rate. Conclusion: Single-session ERCP and cholecystectomy are feasible and effective, especially in rural or resource-constrained settings. However, slightly elevated complication rates call for broader multicenter studies and standardization.